Prevalence and geographical distribution of insulin pump therapy in the Central Denmark Region and its association with metabolic parameters. (July 2018) - Kampmann, Ulla; Madsen, Lene Ring; Bjerg, Lasse; Witte, Daniel R.; Hasselstrøm, Kjeld; Østergård, Torben; Alstrup, Kirsten; Møller, Marianne Kleis; Dylmer, Dorrit; Hansen, Klavs Würgler
Abstract: Aims: Insulin treatment in type 1 diabetes encompasses multiple daily insulin injections (MDI) or continuous subcutaneous insulin infusion (CSII). Both population-based studies and comparative studies regarding CSII use are sparse. The aim of the current study was to describe the prevalence and distribution of CSII use among adults with type 1 diabetes in the Central Denmark Region and to compare metabolic control in CSII-treated patients to those treated with MDI. Methods: A database was constructed using the Danish Adult Diabetes Registry in 2014/2015 in combination with an audit of the patients' medical records. Results: 3909 adults with type 1 diabetes patients were included. The proportion of patients treated with CSII differed significantly between the 8 regional hospitals from 12.0% to 31.1%. CSII users had a significantly lower HbA1c compared to MDI treated patients (7.6% (60 mmol/mol) versus 8.0% (64 mmol/mol)) in unadjusted analyses. After adjustment for clinically relevant characteristics the difference between CSII and MDI-treated patients was attenuated, but remained statistically significant. Conclusion: The distribution of CSII differed markedly between hospitals and CSII users had better glycemic control, even after adjustment for sex, age, BMI, diabetes duration, smoking, use of lipid-lowering and blood pressure-lowering medication.